Synthesis of New Bis-Spiropyrazoles as Antitumor Agents under Ultrasound Irradiation - Abdel Hafez, Naglaa A.; Hassaneen, Huwaida M.E.; Farghaly, Thoraya A.; Riyadh, Sayed M.; Elzahabi, Heba S.A. (Mini Reviews in Medicinal Chemistry, 2018)
Objective and Background: Hydrazonoyl halides were used as precursors for the synthesis of a new series of bis-spiropyrazoles via reaction with 3,5-diarylidene-piperidone derivatives under ultrasound irradiation. The products were secluded in good yield after short reaction periods. Conclusion: The anticancer activity of bis-spiropyrazoles against HepG2 (hepatic cancer), A549 (lung cancer) and CaCo2 (colon cancer) cell lines was screened. Three tested compounds 4b, 4c and 4f showed promising activity.
Keywords: hydrazonoyl halides